2009
DOI: 10.1103/physrevb.79.075302
|View full text |Cite
|
Sign up to set email alerts
|

Indium surface diffusion on InAs(2×4)reconstructed wetting layers on GaAs(001)

Abstract: In this paper we present a study of In surface diffusion on InAs wetting layers deposited on the ͑001͒ surface of GaAs. The ␣ 2 ͑2 ϫ 4͒ and ␤ 2 ͑2 ϫ 4͒ reconstructions stabilized by a high In concentration are considered. The low symmetry of the ␣ 2 ͑2 ϫ 4͒ reconstruction allowed us to understand the effect of the wetting-layer symmetry on the adsorbate diffusion. We find that ͑i͒ the diffusion coefficient value is larger for In motion on the ␣ 2 reconstruction than on the ␤ 2 reconstruction. This is due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 30 publications
3
19
0
Order By: Relevance
“…The values of the maximum energy barriers along either pathway ͑0.26 and 0.29 eV, respectively͒ are comparable to those calculated earlier for In diffusion on an In 2/3 Ga 1/3 As wetting layer on GaAs͑001͒ with ͑2 ϫ 3͒ reconstruction 21 and somewhat lower than the barriers reported for In diffusion on InAs͑001͒ in the ␤2͑2 ϫ 4͒ reconstruction 23 and In diffusion on the ␤2͑2 ϫ 4͒ reconstructed wetting layer ͑1.75 ML InAs͒ on GaAs͑001͒. 22,24 We note that the energy barriers for "uphill" diffusion and "sideways" diffusion are of comparable size, i.e., long-range diffusion on the unstrained InAs͑137͒ surface is nearly isotropic.…”
Section: A In Adatom Diffusion On Inas(137)supporting
confidence: 88%
“…The values of the maximum energy barriers along either pathway ͑0.26 and 0.29 eV, respectively͒ are comparable to those calculated earlier for In diffusion on an In 2/3 Ga 1/3 As wetting layer on GaAs͑001͒ with ͑2 ϫ 3͒ reconstruction 21 and somewhat lower than the barriers reported for In diffusion on InAs͑001͒ in the ␤2͑2 ϫ 4͒ reconstruction 23 and In diffusion on the ␤2͑2 ϫ 4͒ reconstructed wetting layer ͑1.75 ML InAs͒ on GaAs͑001͒. 22,24 We note that the energy barriers for "uphill" diffusion and "sideways" diffusion are of comparable size, i.e., long-range diffusion on the unstrained InAs͑137͒ surface is nearly isotropic.…”
Section: A In Adatom Diffusion On Inas(137)supporting
confidence: 88%
“…5) and those obtained using LDA (see Ref. [15]) can be ascribed mainly to two factors: (i) GGA tends to overestimate the lattice mismatch between InAs and GaAs, as already shown before. Thus, GGA overestimates the compressive strain effects, whereas LDA underestimates them.…”
Section: Diffusionmentioning
confidence: 86%
“…[13,15], where the occupation probability P i (t) of each site i is found from the solution of the master equation for the transition state matrix, that takes into account all the transition rates Γ ji between the adsorption sites of the In PES.…”
Section: Diffusionmentioning
confidence: 99%
“…The elongation orientation is in [110] direction due to the faster In adatom surface diffusion on an As-stabilized surface. 10,28 The density of the InAs QDashes is 5.1 Â 10 10 cm À2 . As we increase the GI time from 0 s to 10 s, it was observed that the InAs nanostructure reorganizes the structure into more round-shapes with increased heights.…”
Section: -3mentioning
confidence: 99%